Computation Graphs for AAD and Machine Learning Part I: Introduction to Computation Graphs and Automatic Differentiation. Issue 104 (12th November 2019) - Savine, Antoine
Abstract : First in a series of three articles with code, exploring the notion of computation graph, with words mathematics and code, and application in Machine Learning and finance to compute a vast number of derivative sensitivities with spectacular speed and accuracy.